2004
DOI: 10.22495/cocv1i3p9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of board characteristics on earnings management

Abstract: This paper examines the relationship between board characteristics and earnings management. Management of a firm may engage in earnings management for his own benefit. However, under proper corporate governance mechanism, the board of directors might be able to monitor the firm and prevent the management from engaging in earnings management. We find that when the board size is large, the higher the extent of earnings management. However, when there are more outside directors in the board, the extent of earning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
57
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 25 publications
19
57
1
3
Order By: Relevance
“…We arrive at various results, some of which confirm existing empirical work done by fellow researchers, in addition to some new results that shed new light on the complex CG relationship with performance. We have found that board size is positively linked with a high TQ ratio, which aligns with previous findings (Dalton et al, 1999;Kao and Chen, 2004;Lipton and Lorsch, 1992;Rahman and Ali, 2006). The size of the board was measured by the number of directors in it.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We arrive at various results, some of which confirm existing empirical work done by fellow researchers, in addition to some new results that shed new light on the complex CG relationship with performance. We have found that board size is positively linked with a high TQ ratio, which aligns with previous findings (Dalton et al, 1999;Kao and Chen, 2004;Lipton and Lorsch, 1992;Rahman and Ali, 2006). The size of the board was measured by the number of directors in it.…”
Section: Discussionsupporting
confidence: 92%
“…Board size is recognized as linked with the performance of firms, yet the existing evidence has produced mixed results, with some studies supporting large boards and others advocating smaller boards. Kao and Chen (2004) have found that a larger board size has the potential to weaken its functioning, and hence its performance, because large boards may be characterized by difficulties in achieving efficient communication between members. Yermack (1996) studied and analysed the governance and financial data of 452 large US firms between 1984 and 1991 and reported an inverse relationship between board size and firms' TQ value.…”
Section: Board Size and Performancementioning
confidence: 99%
“…The result of this study supports the results of Kao and Chen 2004;Davidson et al 2005 andJaggi et al 2007). …”
Section: Asian Journal Of Finance and Accountingsupporting
confidence: 91%
“…Therefore, boards with more independent outside directors are in a better position to increase monitoring and controlling the opportunistic behavior of managers (Jensen and Meckling, 1976). Several previous studies have argued that independent board constitutes a constraint on earnings management (Jouber and Kao and Chen (2004) and Ebrahim (2007) find that larger boards are associated with lower levels of discretionary accruals. We have not predicted the sign of this association.…”
Section: Effect Of the Board Characteristics On Earnings Managementmentioning
confidence: 97%